Implementasi Metode Inquiry dalam Pembelajaran Agama Katolik - Anastasia Manalu; Sergius Lay; Megawati Naibaho; Alexius Poto Obe (Journal New Light, 2025)
This article aims to provide an in-depth review of the implementation of the inquiry method in Catholic Religious Education. The study applies a systematic literature review approach by analyzing various relevant sources, including books, indexed journal articles, and official documents of the Catholic Church published within the last five years. The inquiry method is considered an effective approach to fostering critical thinking, creativity, and active participation of learners in understanding the values of the Catholic faith. Data analysis was conducted through reduction, classification, and synthesis to explore the relevance of inquiry implementation in the context of religious education. The findings indicate that the inquiry method encourages students not only to receive the faith teachings passively but also to reflect on their life experiences in the light of the Gospel. This strategy strengthens faith identity, builds reflective thinking skills, and promotes a dialogical attitude in facing contemporary challenges. The article concludes that the inquiry method can serve as an effective pedagogical alternative in Catholic Religious Education, although its application requires adaptation to theological contexts, spirituality, and Catholic school curricula. Thus, this review is expected to contribute to both theoretical development and practical innovation in the teaching of religion in contemporary contexts.